2016
DOI: 10.19082/2982
|View full text |Cite
|
Sign up to set email alerts
|

Assosiation of Epicardial and Pericardial Fat Thickness with Coronary Artery Disease

Abstract: IntroductionVisceral adipose tissue is a known important risk factor for coronary artery disease (CAD). While some studies have suggested relationship between epicardial fat thickness (EFT) and CAD, there are no adequate studies for pericardial fat thickness (PFT). The aim of this study was to determine the association of EFT and PFT with CAD.MethodsThis cross-sectional study was conducted on patients who were candidates for elective coronary artery angiography, referred to Emam Reza Hospital, Mashhad, Iran du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 28 publications
(66 reference statements)
2
10
0
Order By: Relevance
“…Surprisingly, the present meta-analysis demonstrated a significant difference in EFT thickness between two groups with and without AF recurrence; similar to what was reported by CT about EFT volumes. These findings put emphasis on the importance of further evaluations on EFT reports about echocardiography, as a safe and non-invasive imaging modality [29]. Furthermore, the present study, as the first attempt to clarify the association between EFT and AF recurrence revealed a new possible imaging marker for the prediction of AF recurrence, which required further carefully-designed studies for more accurate evaluations.…”
Section: Discussionmentioning
confidence: 77%
“…Surprisingly, the present meta-analysis demonstrated a significant difference in EFT thickness between two groups with and without AF recurrence; similar to what was reported by CT about EFT volumes. These findings put emphasis on the importance of further evaluations on EFT reports about echocardiography, as a safe and non-invasive imaging modality [29]. Furthermore, the present study, as the first attempt to clarify the association between EFT and AF recurrence revealed a new possible imaging marker for the prediction of AF recurrence, which required further carefully-designed studies for more accurate evaluations.…”
Section: Discussionmentioning
confidence: 77%
“…Ghaderi et al demonstrated a relation between coronary disease assessed angiographically with echocardiographically measured epicardial adipose tissue thickness. A study performed on a group of 100 patients demonstrated that patients with significantly narrowed coronary arteries were characterized by significantly greater thickness of the epicardial adipose tissue, compared with the patients without significant stenosis in the coronary arteries [ 15 ]. Moreover, this study documented a relation between coronary disease risk factors and the EATT, as well as between the number of atherosclerotic coronary arteries and the EATT [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…The pericardial adipose tissue (PAT) is located in the pericardium and is a type of visceral fat that has attracted much attention from many researchers in recent years [ 8 , 9 ]. Several studies on PAT have focused on the relationship between PAT volume and heart disease [ 10 - 12 ].…”
Section: Introductionmentioning
confidence: 99%